Covalently functionalized DNA duplexes and quadruplexes as hybrid catalysts in an enantioselective Friedel-Crafts reaction - Dey, Surjendu; Jäschke, Andres (Molecules, 2020)
The precise site-specific positioning of metal-ligand complexes on various DNA structures through covalent linkages has gained importance in the development of hybrid catalysts for aqueous-phase homogeneous catalysis. Covalently modified double-stranded and G-quadruplex DNA-based hybrid catalysts have been investigated separately. To understand the role of different DNA secondary structures in enantioselective Friedel-Crafts alkylation, a well-known G-quadruplex-forming sequence was covalently modified at different positions. The catalytic performance of this modified DNA strand was studied in the presence and absence of a complementary DNA sequence, resulting in the formation of two different secondary structures, namely duplex and G-quadruplex. Indeed, the secondary structures had a tremendous effect on both the yield and stereoselectivity of the catalyzed reaction. In addition, the position of the modification, the topology of the DNA, the nature of the ligand, and the length of the linker between ligand and DNA were found to modulate the catalytic performance of the hybrid catalysts. Using the optimal linker length, the quadruplexes formed the (-)-enantiomer with up to 65%ee, while the duplex yielded the (+)-enantiomer with up to 62%ee. This study unveils a new and simple way to control the stereochemical outcome of a Friedel-Crafts reaction.
Gesehen am 30.09.2020